2021
DOI: 10.1111/ene.15189
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of electroencephalographic neurofeedback for people with chronic pain: A systematic review and meta‐analysis

Abstract: Background Electroencephalographic (EEG) neurofeedback has been utilized to regulate abnormal brain activity associated with chronic pain. Methods In this systematic review, we synthesized the evidence from randomized controlled trials (RCTs) to evaluate the effect of EEG neurofeedback on chronic pain using random effects meta‐analyses. Additionally, we performed a narrative review to explore the results of non‐randomized studies. The quality of included studies was assessed using Cochrane risk of bias tools, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…This study demonstrated a significant effect of ISF-NF up-training pgACC on the effective connectivity when compared to sham-NF training, and furthermore, the amount of information transfer from the pgACC to the S1L was correlated with the amount of pain severity reduction. While only a few previous studies have demonstrated objective neural changes following EEG-NF training [ 9 , 10 , 11 ], our study is the first study to demonstrate evidence of correlations of objective neural changes with improvements in clinical outcomes, thus indicating the specificity of the EEG-NF training.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…This study demonstrated a significant effect of ISF-NF up-training pgACC on the effective connectivity when compared to sham-NF training, and furthermore, the amount of information transfer from the pgACC to the S1L was correlated with the amount of pain severity reduction. While only a few previous studies have demonstrated objective neural changes following EEG-NF training [ 9 , 10 , 11 ], our study is the first study to demonstrate evidence of correlations of objective neural changes with improvements in clinical outcomes, thus indicating the specificity of the EEG-NF training.…”
Section: Discussionsupporting
confidence: 43%
“…To our knowledge, our study is the first double-blinded randomised placebo-controlled trial to explore the effect of EEG ISF-NF on the effective connectivity between the targeted brain regions, and its associations with the changes in clinical outcomes of pain and disability, as these are important and recommended domains for determining the specificity of the EEG-NF training [ 11 ]. This study demonstrated a significant effect of ISF-NF up-training pgACC on the effective connectivity when compared to sham-NF training, and furthermore, the amount of information transfer from the pgACC to the S1L was correlated with the amount of pain severity reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kayiran et al 8 supressed theta (3–8 Hz) while reinforcing low beta (13–15 Hz) that also resulted in pain reduction. A recent meta-analysis found that neurofeedback based on alpha band upregulation result in clinically meaningful reduction of pain but concluded that more studies are required to confirm the results 9 .…”
Section: Introductionmentioning
confidence: 99%